A study of the unequal treatment under the law in the matter of fornication between a Muslim and a non-Muslim in Malaysia / Nik Nadia Nik Ahmad Ariff … [et al.] - Nik Ahmad Ariff, Nik Nadia; M Junim, Brenda Viola; Ab Rahman, Muhamad Faizee; Ahmad Marzulai, Ahmad Maliki; Abdul Gaffoor, Farah Lydia (2010)
This study discusses the inequality before the law in matter of fornication between a Muslim and a non-Muslim in Malaysia, whereby when a Muslim and a non-Muslim couple get caught red-handed in the act of fornication, usually only the Muslim will be punished while the non-Muslim will not. The project analyzes various views including the religious, legal, philosophical and moral aspects regarding the concerned issue. Apart from that, effects of fornication which consist of medical, psychological and also societal implications are also discussed. At the end of this project, it is suggested that fornicators, Muslim or non-Muslim to be equally treated or punished under the law.